2008
DOI: 10.1073/pnas.0803027105
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric mitosis: Unequal segregation of proteins destined for degradation

Abstract: Mitotic cell division ensures that two daughter somatic cells inherit identical genetic material. Previous work has shown that signaling by the Smad1 transcription factor is terminated by polyubiquitinylation and proteasomal degradation after essential phosphorylations by MAPK and glycogen synthase kinase 3 (GSK3). Here, we show that, unexpectedly, proteins specifically targeted for proteasomal degradation are inherited preferentially by one mitotic daughter during somatic cell division. Experiments with divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 29 publications
4
140
0
Order By: Relevance
“…The observation that pMad-Gsk is present only in pH3-positive mitotic cells during larval wing development fits with the work of Fuentealba et al (2008) who noted pSmad1-Gsk expression only during self-renewing divisions of human embryonic stem cells. Furthermore, their data revealed that pSmad1-Gsk is asymmetrically segregated into only one of the daughter cells during these divisions.…”
Section: Discussionsupporting
confidence: 68%
“…The observation that pMad-Gsk is present only in pH3-positive mitotic cells during larval wing development fits with the work of Fuentealba et al (2008) who noted pSmad1-Gsk expression only during self-renewing divisions of human embryonic stem cells. Furthermore, their data revealed that pSmad1-Gsk is asymmetrically segregated into only one of the daughter cells during these divisions.…”
Section: Discussionsupporting
confidence: 68%
“…MZ twin pairs are living human laboratories, and when they begin to diverge phenotypically, we can discover new ways in which the genome/epigenome profoundly changes post-zygotically. Some of these divergences occur in embryonic stem cells soon after zygosis [Fuentealba et al, 2008], perhaps in concert with events that underlie determination and differentiation of axes, organs, and tissues during embryogenesis. It is not clear whether any or most of these divergences actually stimulate the MZ twinning process.…”
Section: Introductionmentioning
confidence: 99%
“…This work sheds light on an important rejuvenation mechanism in mammalian cells and provides new biological insight into the role of inclusion bodies in regulating aggregation, toxicity, and aging. aggregate segregation during mammalian or Drosophila mitosis (12,13,14). The mechanism for directing misfolded proteins to different inclusions structures, however, appears to be at least partially conserved from yeast to mammals.…”
Section: Significancementioning
confidence: 99%